Teachers’ Competence in Lesson Preparation and Presentation in Nigeria Basic Schools - Ajayi, P. O.; Ajayi L, F. (Advances in Social Sciences Research Journal, 2015)
This study assessed the competence of Nigeria Basic School teachers in lesson preparation and presentation. The study employed a descriptive research design. Four research questions were raised and answered. The sample used for the study comprised 200 elementary school teachers chosen from twenty schools in Nigeria. Simple random sampling technique was used to choose the schools as well as the ten teachers per school used. A research instrument focusing on Teachers’ Competence Level in Lesson Preparation and Presentation (TCLLPP) was used to generate data for the study. The results of the findings showed that elementary school teachers in Nigeria are deficient in the knowledge of adequate lesson preparation and presentation. High percentage of the teachers sampled had no adequate knowledge of essential features of lesson note preparation. Based on the findings, it was recommended that elementary school teachers in Nigeria should be given necessary and adequate in-service training on lesson note preparation and presentation